2020
DOI: 10.1186/s12877-020-1481-8
|View full text |Cite
|
Sign up to set email alerts
|

ADL recovery trajectory after discharge and its predictors among baseline-independent older inpatients

Abstract: Background:Among the previous studies about the ADL recovery and its predictors, the researches and resources used to study and protect the baseline-independent older patients from being permanently ADL-dependent was few. We aimed to describe the level of activities of daily living (ADL) at discharge and ADL change within 6 months after discharge in older patients who were ADL-independent before admission but became dependent because of acute illness, and to identify the predictors of early rehabilitation,so a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our approach was aimed at determining the current state of functional disability, as well as the validity and reliability of the chosen measuring instrument, while the study provided by Li et al (2020) used the self-assessment method as a way to monitor the recovery of functional independence in elderly hospitalised persons after discharge from treatment. A similar purpose was found in a study by Covinsky, Palmer, Fortinsky and Counsell (2003), who successfully applied the self-assessment of ADLs and IADLs in determining changes in functional abilities before and after hospitalisation, simultaneously describing the impact of age on functional capacity loss.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach was aimed at determining the current state of functional disability, as well as the validity and reliability of the chosen measuring instrument, while the study provided by Li et al (2020) used the self-assessment method as a way to monitor the recovery of functional independence in elderly hospitalised persons after discharge from treatment. A similar purpose was found in a study by Covinsky, Palmer, Fortinsky and Counsell (2003), who successfully applied the self-assessment of ADLs and IADLs in determining changes in functional abilities before and after hospitalisation, simultaneously describing the impact of age on functional capacity loss.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies generally concluded that disability is an outcome indicator of intrinsic ability loss. The de nitions of the two indicators of activities of daily living (ADL) and instrumental activities of daily living (IADL) measure individuals' ability to independently satisfy their individual functions and use tools to meet them, re ecting to some extent the performance of their functions in their environments [39,40]. Therefore, the sum of ADL and IADL scores is applied to comprehensively re ect a patient's FA.…”
Section: Key Variablesmentioning
confidence: 99%
“…In-hospital characteristics and risk factors were chosen according to the well-documented predictors of acute hospitalization outcomes described in previous studies [4,44]. In the present study these factors include cognitive status at admission, emotional status, functional status in BADL during hospitalization, Length of Hospital Stay (LOS), severity of the acute illness, and symptoms severity.…”
Section: Predictorsmentioning
confidence: 99%